Bias-dependent oscillatory electron transport of monatomic sulfur chains - SANVITO, STEFANO (My University, 2012)
The bias-dependent oscillatory electron transport of monatomic sulfur chains sandwiched between gold electrodes is investigated with density functional theory and non-equilibrium Green's function method. At zero bias, in contrast to the typical odd-even oscillations observed in most metallic chains, we find that the conductance oscillates with a period of four atoms. However, as the bias voltage is increased the current displays a two-atom periodicity. This emerges gradually, first for the longer chains and then, at voltages larger than 0.7 V, for lengths. The oscillatory behaviors are analyzed by the density of states and the energy-dependent and bias-dependent transmission coefficients.
PUBLISHED
Keywords: bias-dependent transmission coefficients; bias-dependent transmission coefficients; Nanoscience & Materials